Spatial distribution of primary outbreaks of highly pathogenic avian influenza in Nigeria (2007)
he geographic coordinates of 116 out of 166 poultry farms (69.9%) with confirm Highly Pathogenic Avian Influenza (HPAI) virus by the National Veterinary Research Institute (NVRI) in Nigeria, out of 629 premises that were screened within 30 States and the Federal Capital Territory (FCT) were used to design a spatial model of the spread of the virus within Nigeria from January 1, 2006 to January 31, 2007. The results showed that 19 of 36 States (52%) of Nigeria were affected with the virus. Movement of personnel from one infected farm to an uninfected farm, transfer of infected birds and contaminated equipment were the main sources of spread of the virus. Thus, there is need to improve the animal health services in Nigeria to attain efficient control of HPAI.